EGR1‐mediated linc01503 promotes cell cycle progression and tumorigenesis in gastric cancer - Ma, Zhonghua (Cell Prolif, 2020)
OBJECTIVES: Long non‐coding RNAs (lncRNAs) are key mediators in various malignancies. Linc01503 was previously elucidated to promote gastric cancer (GC) cell invasion. However, the upstream mechanism of linc01503 and its involvement in GC cell cycle, apoptosis and tumorigenesis still remain unclear. MATERIALS AND METHODS: Bioinformatics analysis and quantitative reverse transcription polymerase chain reaction (qRT‐PCR) assays were implicated to detect linc01503 level in GC. The role of linc01503 was detected by in vitro functional assays and in vivo xenograft tumour models. The association between linc01503 and its upstream effector was identified by chromatin immunoprecipitation (ChIP) assays. The mechanistic model of linc01503 was clarified using subcellular separation, fluorescence in situ hybridization, RNA‐sequencing, RNA immunoprecipitation (RIP) and ChIP assays. RESULTS: Linc01503 was remarkably elevated in GC and tightly linked with the overall survival of patients with GC. The key transcription factor early growth response protein 1 (EGR1) critically activated the transcription of linc01503. Functionally, linc01503 knockdown resulted in the activation of apoptosis and G1/G0 phase arrest in GC. Mechanistically, linc01503 interacted with histone modification enzyme enhancer of zeste 2 (EZH2) and lysine (K)‐specific demethylase 1A (LSD1), thereby mediating the transcriptional silencing of dual‐specificity phosphatase 5 (DUSP5) and cyclin‐dependent kinase inhibitor 1A (CDKN1A) in GC. CONCLUSIONS: EGR1‐activated linc01503 could epigenetically silence DUSP5/CDKN1A expression to mediate cell cycle progression and tumorigenesis, implicating it as a prospective target for GC therapeutics.